A critical analysis of the human rights violations of detainees in South African police custody with specific reference to police brutality - Leeuw, Tembisa (University of the Free State, 2019)
This study analyses the human rights violations of detainees in South African police custody. In so doing, the study focuses on police brutality. In explaining police brutality in custody, different scholars gave a common definition, namely that police brutality is the use of excessive force to cause physical, emotional, mental and deadly harm to a suspect held in custody. Police brutality is the legacy of apartheid from its formation as the Union of South Africa in 1910. The South African Police (SAP) then already adopted the features of a colonial military force, and members were socialized to use excessive force during arrest and to suspects held in custody. A desk review was adopted to gather information from primary sources such as legal documents and secondary sources such as books, academic journals and newspaper articles on police brutality in holding cells. This process was guided by three research objectives: a) to explore the nature and causes of police brutality in South African holding cells; b) to examine the effects of police brutality in South African holding cells; c) to recommend remedial measures to mitigate police brutality in South African holding cells. The findings of this study discovered that police brutality in custody is mostly caused by leadership failure and the non-reporting of cases of police brutality by the police administrators who are responsible for reporting these. In many cases, investigations favour the accused police officer. Police brutality is caused by ineffectual civil remedies. This means that if police officers are not held responsible for their brutality in holding cells they are more likely to persist with this behaviour. Passivity with regards to criminal prosecutions is another issue, as prosecutors often do not want to prosecute officers who usually help them with criminal cases. In explaining victimisation in police custody, three learning theories are relevant. They are the social learning theory, the differential association theory, and the group socialisation theory. These state that police brutality in custody is learned through socialisation and integrating with other violent police officers. The study also makes use of the conflict theory and the routine activity theory to explain what motivates the violation of detainees’ rights in custody. The study further examines the role of the Independent Police Investigative Directorate. In so doing, it analyses the IPID Act (1 of 2011) and its mandate and powers. Since its establishment, the number of cases of police brutality has decreased and more police officers have been held responsible for their misconduct. The study provides recommendations to help mitigate police brutality towards detainees in South Africa.
Dissertation (LL.M.(Human Rights))--University of the Free State, 2019
Keywords: Police; Police brutality; Human rights violations; Custody; Detainees; Victims; Detainees’ rights; Independent Police Investigative Directorate